The impact of the COVID-19 pandemic on quality of life and well-being in Morocco - Samlani Z; Lemfadli Y; Ait Errami A; Oubaha S; Krati K (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Introduction: The majority of epidemiological reports focus on confirmed cases of COVID-19. In this study, we aim to assess the health and well-being of adults not infected with Covid-19 after two months of quarantine in Morocco. Materials and methods: Two months after the declaration of quarantine in Morocco following the Covid-19 epidemic, we carried out a descriptive cross-sectional study of 279 Moroccan citizens. We used the Short Form Health Survey (SF-12) as a determinant of quality of life, which is based on eight dimensions of health. The data were collected using an electronic questionnaire distributed online. The participants also indicated their socio-demographic data, their knowledge and practices regarding the Covid-19 pandemic and whether they had chronic health problems. Results: The quality of life of all participants was moderately disrupted during the Covid-19 pandemic with a mental health score (MCS) of 34.49 (± 6.44) and a physical health score (PCS) of 36.10 (± 5.82). Participants with chronic diseases scored lower with 29.28 (± 1.23) in mental health (MCS) and 32.51 (± 7.14) in physical health (PCS). The seriousness of COVID-19 has an impact on the quality of life and health well-being of people and this impact is more marked in people with chronic health problems. Conclusion: Our results confirm the need to pay attention to the health of people who have not been infected with the virus. Our results also point out that uninfected people with chronic illnesses may be more likely to have well-being problems due to quarantine restrictions.